2019
DOI: 10.1037/ocp0000128
|View full text |Cite
|
Sign up to set email alerts
|

Customer mistreatment harms nightly sleep and next-morning recovery: Job control and recovery self-efficacy as cross-level moderators.

Abstract: Customer mistreatment is becoming an important topic for work stress researchers and practitioners given the rise of service industry. Taking stressor-emotion-control perspectives, the authors examine day-level relationships between call center workers' customer mistreatment experiences and their impaired recovery outcomes mediated by end-of-work negative affect. Furthermore, control concepts in the job and personal domains are tested as cross-level moderators. Specifically, job control and recovery self-effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(95 citation statements)
references
References 69 publications
4
89
1
1
Order By: Relevance
“…Our research shows that for the service employees, WFC and lack of family satisfaction can arise from the unfair and unjust treatment by customers. Irrational and inconsolable customers always exist, and customer mistreatment is thus difficult to prevent (Park and Kim, 2019). However, the organizations should try to reduce the occurrence of customer mistreatment in case of its negative work-family spill-over effects for organizational employees.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our research shows that for the service employees, WFC and lack of family satisfaction can arise from the unfair and unjust treatment by customers. Irrational and inconsolable customers always exist, and customer mistreatment is thus difficult to prevent (Park and Kim, 2019). However, the organizations should try to reduce the occurrence of customer mistreatment in case of its negative work-family spill-over effects for organizational employees.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, from the point-view of emotions, it has been argued (Chi et al, 2018) that individuals who experience customer mistreatment in the workplace may take negative emotions resulting from this mistreatment back home, engendering work-family conflict. Park and Kim (2019) also argued that customer mistreatment’s harmful effects can be extended to the personal life domain. In summary, service employees who are mistreated by customers are prone to experience WFC.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…An early study showed that autonomy (a form of control) could be a moderator to reduce strength of the relationship between stressors and strains (Beehr, 1976), and still others have recently found forms of control to moderate the relationship between stressors and strains (e.g., Brough, Drummond, & Biggs, 2018;Cendales-Avala, Useche, Gómez-Ortiz, & Bocarejo, 2017;Park & Kim, 2019). Overall, however, the evidence for control as a moderator of the relationship between stressors and strains is not consistent (Semmer & Beehr, 2014).…”
Section: Environmental Moderatorsmentioning
confidence: 99%
“…Branden (2017) (Cherian & Jacob, 2013), pengambilan keputusan karier (Betz et al, 1996), perkembangan karier (Dimotakis et al, 2017), dan kepuasan kerja (Klassen & Chiu, 2010). Efikasi diri juga memainkan peran penting terhadap kesehatan manusia, seperti perilaku hidup sehat (Brouwer-Goossensen et al, 2018 (Park & Kim, 2018). Bandura (1982) menjelaskan bahwa efikasi diri yang tinggi memprediksi keberhasilan seseorang dalam meraih tujuannya.…”
unclassified